Supply chain management: the elusive concept and definition. Issue 4 (13th November 2017) - LeMay, Steve; Helms, Marilyn M.; Kimball, Bob; McMahon, Dave
Abstract : Purpose: The purpose of this paper is to gather the current definitions of supply chain management in practical and analytical usage, to develop standards for assessing definitions and to apply these standards to the most readily available definitions of the term. Design/methodology/approach: In this research, the authors gathered the current definitions of supply chain management in practical and analytical usage from journals, textbooks, universities, and industry associations and online. Findings: The research ends with proposed definitions for consideration. Discussion and areas for future research are included. Research limitations/implications: Involved organizations, supply chain management programs in higher education, and professional and certifying organizations in the field need to meet and work together to research consensus on the final definition of the field, realizing that definitions can evolve, but also recognizing that a starting point is needed in this rapidly growing area. Practical implications: The authors argue, quite simply, that a consensus definition of supply chain management is unlikely as long as we continue offering and accepting definitions that are technically unsound. Many of the current definitions violate several principles of good definitions. For these reasons, they are either empty, too restrictive, or too expansive. Until we come across or develop a definition that overcomes these limitations and agree on it, then we will still search for "the" definition without finding it. The field will become more crowded with definitions, but less certain, and progress will be restricted. Originality/value: Theoreticians, researchers, and practitioners in a discipline require key terms in a field to share a nominal definition and prefer to have a shared real or essential definition. Yet in supply chain management, we find no such shared definition, real or nominal. Even the Council of Supply Chain Management Professional offers its definition with the caveat: "The supply chain management (SCM) profession has continued to change and evolve to fit the needs of the growing global supply chain. With the supply chain covering a broad range of disciplines, the definition of what is a supply chain can be unclear" (CSCMP, 2016 ).